2016
DOI: 10.1186/s12885-016-2778-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil implants caused a diaphragmatic tumor to be misdiagnosed as liver metastasis: a case report

Abstract: BackgroundFluorouracil implants are widely used in peritoneal interstitial chemotherapy. Curative effects have been obtained, but implants have also caused some complications.Case presentationWe performed an analysis of a 66-year-old male patient’s case history, as well as conventional pathological analysis and Raman spectroscopic detection of the diaphragmatic tumor. We also analyzed the underlying causes of this condition to prevent complications and reduce misdiagnoses in future cases. The patient had a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Prior studies have reported similar difficulties. Shen et al reported that an FEL implanted in the abdomen for adjuvant chemotherapy was misdiagnosed as liver metastasis in a patient with colon cancer ( 16 ). In another case report ( 15 ), FEL put surrounding the liver during the resection of gastric adenocarcinoma was mistaken for a liver tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported similar difficulties. Shen et al reported that an FEL implanted in the abdomen for adjuvant chemotherapy was misdiagnosed as liver metastasis in a patient with colon cancer ( 16 ). In another case report ( 15 ), FEL put surrounding the liver during the resection of gastric adenocarcinoma was mistaken for a liver tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Without a multidisciplinary team (MDT) discussion concerning the nature of such lesions, oncologists and surgeons can easily be misled by radiological findings and potentially erroneous reporting, leading to unnecessary additional treatment. Two previous case reports described fluorouracil encapsulated lesion (FEL) being misdiagnosed as a liver tumor, after which surgical resection was performed ( 15 , 16 ). However, the imaging characteristics of FELs have not been characterized or compared with those of liver metastases in a systematic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical examination of the fibrotic mass showed that it contained fluorouracil. This rare complication of SinoFuan® implants shows the need for better understanding the cause of this problem and improving the application of such implants in different gastric cancer [157].…”
Section: Plga-based Long Acting Biodegradable Systemsmentioning
confidence: 99%
“…The biggest problem is that the drug release rate (DRR) of Zoladex ® implant is unstable (Lu et al., 2020 ). Sinofuan ® is the first fluorouracil sustained-release implant approved by China FDA for clinical treatment of colorectal cancer (Shen et al., 2016 ). It is a micro-cylindrical rod matrix implant prepared by blending silicone rubber and 5-fluorouracil, so its biggest problem is that it cannot be degraded in the body.…”
Section: Introductionmentioning
confidence: 99%